1988
DOI: 10.1113/jphysiol.1988.sp017336
|View full text |Cite
|
Sign up to set email alerts
|

Bistability of alpha‐motoneurones in the decerebrate cat and in the acute spinal cat after intravenous 5‐hydroxytryptophan.

Abstract: SUMMARY1. In the preceding paper (Crone, Hultborn, Kiehn, Mazieres & Wigstr6m, 1988) it was shown that a short-lasting synaptic excitation ('on' stimulus) of extensor motoneurones (primarily triceps surae) in the decerebrate cat often resulted in a maintained excitability increase, which could be reset by a short-lasting inhibitory stimulus train ('off' stimulus). In the present experiments intracellular recording from triceps surae motoneurones and the electroneurogram (ENG activity) from triceps surae nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
542
3
12

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 638 publications
(584 citation statements)
references
References 24 publications
27
542
3
12
Order By: Relevance
“…6 D). This pattern resembles that observed in spinal motoneurons in the presence of serotonin, which has been linked to a nifedipine-sensitive calcium current (Hounsgaard et al, 1988;Hounsgaard and K iehn, 1989). The actual mechanism generating depolarizing plateau in L ugaro cells may thus involve a modulation of both potassium and calcium currents, or may even be more complicated, as for the calcium-dependent afterdepolarization mediated by I h in thalamic neurons (L üthi and McCormick, 1999).…”
Section: Serotonin Transforms Inactive Lugaro Cells Into Regular Spikmentioning
confidence: 85%
“…6 D). This pattern resembles that observed in spinal motoneurons in the presence of serotonin, which has been linked to a nifedipine-sensitive calcium current (Hounsgaard et al, 1988;Hounsgaard and K iehn, 1989). The actual mechanism generating depolarizing plateau in L ugaro cells may thus involve a modulation of both potassium and calcium currents, or may even be more complicated, as for the calcium-dependent afterdepolarization mediated by I h in thalamic neurons (L üthi and McCormick, 1999).…”
Section: Serotonin Transforms Inactive Lugaro Cells Into Regular Spikmentioning
confidence: 85%
“…Recognizing that activity in descending serotonergic pathways was decreased in the commonly used anesthetised cat preparation (Engberg et al, 1968), Hultborn and colleagues attempted to evoke plateau potentials in this preparation, but were unable to do so. Following administration of 5-HTP to enhance serotonergic transmission, or clonidine to mimic noradrenergic transmission, however, plateau potentials could indeed be evoked in anesthetised animals (Conway et al, 1988;Crone et al, 1988;Hounsgaard et al, 1988). The conclusion drawn from these experiments was that monoamines are required for expression of plateau potentials.…”
Section: The Role Of Motoneuron Dendrites In Repetitive Firingmentioning
confidence: 89%
“…The spinal cord could then be removed and motoneuron properties studied in vitro. In the acutely transected spinal cord, PICs are not present in either cat lumbar motoneurons (Hounsgaard et al, 1988) or rat sacral motoneurons (Bennett et al, 2001). Following chronic injury, however, Bennett et al (2001) showed that PICs are readily expressed.…”
Section: The Role Of Motoneuron Dendrites In Repetitive Firingmentioning
confidence: 94%
See 1 more Smart Citation
“…Plateau potentials are mediated by nifedipine-sensitive Ct* entry through L-type channels (Hounsgaard and Kiehn, 1989). In turtle and cat motoneurons bistability is not an endogenous property, but is dependent upon the presence of monoamines (Hounsgaard et al, 1988;Conway et al, 1988). Thus the modulatory action of 5-HT, and possibly the other monoamines, on NMDA currents and bistability probably plays a considerable role in the initiation and the regulation of locomotion.…”
mentioning
confidence: 99%